The Effect Of Internal Measures Of Service Quality On Business Performance: A Case Of Hotel Industry In Malaysia. - Zailani, Suhaiza; Hj Din, Saari; Abd Wahid, Nabsiah (2006)
Hotel industry and tourism sector is to be seen as symbiotic interrelated. They have played a significant role in transformation of business activities that share the bulk of today's economy.